Estudio del consumo de sustancias psicoactivas en la Universidad Nacional de Manizales (1997)
ABSTRACT: The purpose of this study was to identify the prevalence and pattern of psychoactive substance use among students of the Universidad Nacional at Manizalez. Of 2963 students enrolled, a sample of 550 was selected. Of those, 329 answer the survey questionnaire. It was found that 256 (77.8%) of them reported lifetime use of any psychoactive substance. The most commonly used substances were alcohol, tobacco, and marihuana. Among alcoholic beverages the most frequenly used were "aguardiente", rum, and beer. Results of the pattern of alcohol and drug use will be presented.